Acute effect of high-calcium milk with or without additional magnesium, or calcium phosphate on parathyroid hormone and biochemical markers of bone resorption - Green, J H; Booth, C; Bunning, R (European journal of clinical nutrition, 2003)
Objective : To assess whether there are any differences in the postprandial physiological responses to apple drink (control), calcium phosphate (tricalcium phosphate, TCP) and high-calcium skim milk (HCSM) with or without additional magnesium in postmenopausal women. Design : Randomized, controlled, cross-over. Measurements after overnight fast before each drink, and subsequently every hour for 8 h postprandially. Setting : Human Nutrition Studies Laboratory, Milk and Health Research Centre, Massey University, Palmerston North, New Zealand. Subjects : Twenty-one healthy postmenopausal women. Interventions : Four drinks, each 400 ml. (1) Apple drink (25% fruit juice). (2) TCP dispersed in water containing 1200 mg Ca. (3) HCSM containing 1200 mg Ca and 65.5 mg Mg. (4) HCSM containing 1200 mg Ca and 172 mg Mg. Results : There was no difference in baseline serum calcium, PTH or C-telopeptide levels between drinks. There were no overall differences in serum calcium after apple or after either milk, but after TCP serum calcium increased from a baseline value of 2.12±0.08 to a mean peak of 2.21±0.12 mmol/l (s.d.) ( P =0.0001) after 2 h. There were no significant differences in serum PTH after either apple or HCSM+Mg. In contrast, after TCP, serum PTH decreased from 2.76±0.69 to a mean nadir of 2.23±0.65 pmol/l ( P =0.0001) after 1 h, and after HCSM, it decreased from 2.71±0.78 to a mean nadir of 2.51±0.87 pmol/l ( P =0.007) after 2 h. Serum C-telopeptides decreased after each drink, reaching nadirs after 5 h. At this time the serum values for each of the high calcium drinks were not different from each other, but were significantly less than for apple ( P =0.001 for each), being 0.22±0.09 ng/ml for apple, 0.15±0.08 for TCP, 0.14±0.07 for HCSM and 0.16±0.07 for HCSM+Mg. Conclusion : Despite differences in serum calcium and PTH responses to the three high-calcium drinks that we tested, there was no distinguishable difference in serum C-telopeptides between high calcium drinks. Sponsorship : New Zealand Milk.